Assessing the Effectiveness of Mycelium-Based Thermal Insulation in Reducing Domestic Cooling Footprint: A Simulation-Based Study - Shouq Al-Qahtani; Muammer Koç; Rima J. Isaifan (Energies)
Domestic cooling requirements in arid and hot climate regions present a substantial challenge in minimizing energy consumption and reducing carbon emissions, largely due to the extensive dependence on electricity-intensive air conditioning systems. The limitations and inefficiencies of traditional construction and insulation materials, coupled with their improper application, further intensify the challenges posed by extreme climatic conditions. Considering these challenges, this study thoroughly assesses a novel and unconventional solution recently introduced for improving insulation: mycelium-based thermal insulation. Mycelium is the growth form of filamentous fungi, capable of binding organic matter through a network of hyphal microfilaments. This research utilizes DesignBuilder v7.3.1.003 simulation software to assess the thermal performance of residential buildings that incorporate mycelium as an insulator. The aim is to compare its efficacy with commonly used traditional insulators in Qatar and to investigate the potential of mycelium as an eco-friendly solution for minimizing thermal energy consumption, enhancing thermal comfort, decreasing carbon emissions, and achieving annual thermal energy savings. This study examines various insulation materials and accentuates the unique advantages offered by mycelium-based composites. Simulation results indicate that the placement of mycelium on both the inner and outer surfaces results in significant annual energy savings of 8.11 TWh, accompanied by a substantial reduction in CO2 emissions.